2013
DOI: 10.1371/journal.pone.0079293
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Traditional Medicinal Plant Extracts with Novel Anti-Influenza Activity

Abstract: The emergence of drug resistant variants of the influenza virus has led to a need to identify novel and effective antiviral agents. As an alternative to synthetic drugs, the consolidation of empirical knowledge with ethnopharmacological evidence of medicinal plants offers a novel platform for the development of antiviral drugs. The aim of this study was to identify plant extracts with proven activity against the influenza virus. Extracts of fifty medicinal plants, originating from the tropical rainforests of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 43 publications
1
63
0
1
Order By: Relevance
“…As an example, influenza viruses are highly infectious and constitute a major causative agent for recurrent epidemics and pandemics. On average, approximately 10% of the world's population is infected by the virus annually, resulting in an estimated 250,000 deaths, hence posing a serious health threat (Rajasekaran et al, 2013). Moreover, new and re-emerging infectious viral diseases are a rising global health threat, and the risk of spreading these viruses between continents and countries is even greater.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, influenza viruses are highly infectious and constitute a major causative agent for recurrent epidemics and pandemics. On average, approximately 10% of the world's population is infected by the virus annually, resulting in an estimated 250,000 deaths, hence posing a serious health threat (Rajasekaran et al, 2013). Moreover, new and re-emerging infectious viral diseases are a rising global health threat, and the risk of spreading these viruses between continents and countries is even greater.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses are one of the major infective agents causing various health problems to humans resulting in death every year (Rajasekaran et al, 2013). Among the viral diseases influenza plays a vital role in humans and animals causing serious illness and major financial strain/stress.…”
Section: Introductionmentioning
confidence: 99%
“…Present review reported plant extracts likely to be promising candidates in the race of developing thirdgeneration anti-influenza drugs, thus challenging the neuraminidase drug-resistant viruses in an effort to protect human health and the global economy. [49] Present review showed that the Himalayan plants contain several bioactive substances like monoterpenoids, flavonoids, triterpenoids, iridoid glycosides, sesquiterpenes, benzoic and phenolic compounds having strong antiviral activity. Among traditionally used medicinal plants of the Himalayan region, phytochemicals of only four plants (Justicia adhatoda, Ocimum basilicum, Plantago major and Zingiber officinale) have been directly checked against viral pathogens ( Table 2).…”
Section: Herb/flower Powder Of Dried Flowers Is Givenmentioning
confidence: 99%